2013
DOI: 10.1063/1.4772965
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and simulation research on self-stabilizing secondary electron emission process across solid dielectrics in vacuum

Abstract: Recently, the cathode-like luminescence phenomena are observed from the surface of solid dielectrics under steady-state high voltage excitation in vacuum, which is closely related to the self-stabilizing secondary electron emission (SSEE) occurring on insulator surface. In this paper, the theoretical analysis about surface charging based on the SSEE is made, and a one-dimensional Mont Carlo simulation on surface charge accumulation under DC voltage excitation is provided. The results reveal that surface chargi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…By contrast, the δ max and corresponding A max of the CuO@PI/SrO@PI/MgO@PI/Al 2 O 3 @PI coated films are 1.59/1.58/1.71/2.02 and 400/300/200/300 eV, respectively. It has been demonstrated that the SEE plays a dominant role in determining the flashover discharge development process, and the reduction of SEY is usually favorable for flashover mitigation. ,, This is because lower SEY inhibits the formation of the SEEA and hence the subsequent desorbed gas breakdown. Analytical flashover theory suggests that the flashover voltage increases with lower SEY, with the voltage approximately proportional to the square root of the term A max δ max A 0 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, the δ max and corresponding A max of the CuO@PI/SrO@PI/MgO@PI/Al 2 O 3 @PI coated films are 1.59/1.58/1.71/2.02 and 400/300/200/300 eV, respectively. It has been demonstrated that the SEE plays a dominant role in determining the flashover discharge development process, and the reduction of SEY is usually favorable for flashover mitigation. ,, This is because lower SEY inhibits the formation of the SEEA and hence the subsequent desorbed gas breakdown. Analytical flashover theory suggests that the flashover voltage increases with lower SEY, with the voltage approximately proportional to the square root of the term A max δ max A 0 1 .…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that the SEE plays a dominant role in determining the flashover discharge development process, and the reduction of SEY is usually favorable for flashover mitigation. 22,63,64 This is because lower SEY inhibits . 21 Here A 0 is a known constant.…”
Section: Experimental Validation Of Trap Modulation and Flashover Mit...mentioning
confidence: 99%
“…Since numerous existing simulations and theories of SEEA are 2D2V, a simplified 2D angular distribution function were more frequently adopted in a range of studies: f 0 (α 0 ) = 0.5cos(α 0 ), with α 0 ∈(−0.5π, 0.5π), as shown in Figure 3a [18,32,33]. The two different treatments will be further compared below to show their influences on the expression of tan(θ).…”
Section: D3v Saturated Secondary Electron Emission Modelmentioning
confidence: 99%
“…Since numerous existing simulations and theories of SEEA are 2D2V, a simplified 2D angular distribution function were more frequently adopted in a range of studies: 𝑓 ′ (𝛼 ′ ) = 0.5cos (𝛼 ′ ), with 𝛼 ′ ∈ (−0.5π, 0.5π), as shown in Figure 3(a) [18,32,33]. The two different treatments will be further compared below to show their influences on the expression of tan(𝜃).…”
Section: • D𝛺mentioning
confidence: 99%